Speeding up deep neural network training with decoupled and analytic learning - Zhuang, Huiping (Nanyang Technological University, 2021)
Training deep neural networks usually demands a significantly long period of time. In this thesis, we explore methods in two different areas, i.e., decoupled learning and analytic learning, in order to reduce the training time.